Sociocultural discourses about love in Portugal: a generational path? - Dias, Ana Rita (2014)
In the present study we aim to understand how people conceptualize and experience love and intimate relationships. The study involved 28 subjects, with whom we conducted an individual interview about their lives’ love story. We compare the speech of young subjects and adults from different generations, also considering their civil status and sex. We found some generational differences and we discuss them under the different historical, social and political background. We conclude that there is a consensual discourse about love, widely shared, as well as a return to more traditional and conventional conceptions about love and relationships - more marked and with more asymmetry and inequality in the youngsters. DOI: http:/dx.doi.org/10.17575/rpsicol.v28i1.618